PENGARUH CAR, LDR, DAN BOPO TERHADAP NET INTEREST MARGIN DENGAN ROE SEBAGAI VARIABEL MODERASI - Widay Wijaksana, I Gusti Ngurah; Sri Harta Mimba, Ni Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
Banks as intermediary institutions must have good financial performance. Good financial performance and good management of funds by the bank can increase public confidence in the bank. Currently, banks are required to find ways and strategies to fulfill the policies set by the Financial Services Authority (OJK). This research uses quantitative methods. The data used in the form of secondary data obtained from data on the financial statements of banks listed on the IDX and inflation data published by Bank Indonesia. The sampling technique used in this research is purposive sampling technique. The hypothesis was tested using Moderated Regression Analysis (MRA). This research was conducted at banks listed on the Indonesia Stock Exchange (IDX) from 2015 to 2020. The results of this study are that CAR has a positive effect on NIM. LDR has a negative effect on NIM. BOPO has a positive effect on NIM. ROE weakens the positive effect of CAR on NIM. ROE does not moderate the negative effect of LDR on NIM. ROE strengthens the positive effect of BOPO on NIM